Pengaruh Kualitas Laba Akuntansi Terhadap Efisiensi Investasi Dengan Risiko Litigasi Sebagai Pemoderasi Pada Perusahaan Sektor Property dan Real Estate Di Indonesia - Efrinal -; Puji Wulandari (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2019)
Litigation risk reducing agency problems and promote greater earnings quality. So the higher the risk of litigation a company, it will increase the value of earnings quality and efficiency of investment. Managers avoid litigation because it can lead to charges. The study used a sample of propety and real estate company listed on the Indonesia Stock Exchange (BEI) in the form of financial statements of 2011-2015. Total final sample used in this study as many as 70 data from 15 property companies. The analysis technique used is the analysis Moderated Regresion Analysis (MRA). These results indicate that the quality of accounting earnings significant positive effect on the efficiency of investment. This positive influence states that the higher quality of earnings will further improve the efficiency of the investment company. While the risk of litigation negative influence the quality of the accounting profit on the efficiency of investment. This negative effect states that the higher the risk of litigation will reduce the value of the quality of the accounting profit on the efficiency of investment. These results indicate that the risk of litigation is able to be a moderating variable between earnings quality on the efficiency of investment